Why school students choose and reject science: a study of the factors that students consider when selecting subjects. Issue 6 (13th April 2017) - Palmer, Tracey-Ann; Burke, Paul F.; Aubusson, Peter
ABSTRACT: Student study of science at school has been linked to the need to provide a scientifically capable workforce and a scientifically literate society. Educators, scientists, and policymakers are concerned that too few students are choosing science for study in their final years of school. How and why students choose and reject certain subjects, including science, at this time is unclear. A Best–Worst Scaling (BWS) survey was completed by 333 Year 10 (age 14–17) students to investigate the relative importance of 21 factors thought to impact students' subject-selection decisions. Students ranked enjoyment, interest and ability in a subject, and its perceived need in their future study or career plans as the most important factors in both choosing and rejecting subjects. They considered advice from teachers, parents or peers as relatively less important. These findings indicate that enhancing students' enjoyment, interest, and perceptions of their ability in science, as well as increasing student perceptions of its value in a future career, may result in more students studying science at school.